Green Demarketing Taking Off: A new environmental CSR approach for airlines - Blanco Sánchez, Azucena (Trinity College Dublin, 2019)
The current growth in climate crisis awareness is forcing industries to shift and adapt their business models to a more sustainable one that satisfies customers’ needs. The airline industry, being one of the industries that contributes to high levels of CO2, has recently received a large amount of criticism. This dissertation attempts to understand customers’ behaviour towards environmental CSR (Corporate Social Responsibility) practices in the airline industry that might affect their purchase behaviour. At the same time, this dissertation strives to provide suitable marketing implications for the airline industry. The data collected from the structured survey is used to find out new marketing practices for the airline industry and to identify segments of the population to whom airlines should engage by using the environmental marketing approach that this study proposes. The most relevant finding is the discovery that demarketing practices might be generally accepted by passengers. The findings contribute to the existing knowledge by covering the gaps in understanding customer behaviour and purchase intention (regarding airline green marketing) and about green demarketing practices in the airline industry. Finally, the discussion of the findings suggests future lines of research regarding profits and ethics in the adoption of demarketing.
PUBLISHED
Keywords: Smart & Sustainable Planet; Consumer behaviour, society